PENYULUHAN BUDAYA SEBAGAI UPAYA PENGEMBANGAN INDUSTRI KREATIF BERBASIS KEARIFAN LOKAL (STUDI DI KELURAHAN PRINGSEWU SELATAN KECAMATAN PRINGSEWU, KABUPATEN PRINGSEWU) - Ratna Sari, Yuni; Rochana, Erna; Hidayati, Dewi Ayu; Budikahono, Gunawan (Prosiding Pengabdian FISIP Unila, 2012)
Creative industries can create a positive business climate in the context of people who want to change and improve lives. Besides, creative indusries can also build the image and national identity based on a renewable resource. Therefore, to create innovation and creativity based on local wisdom is a competitive excellence of  a nation. Efforts of developing creative industries based on local wisdom would give a positive social impact in which they would be able to  improve the quality of life. Moreover the increase and improvement in quality of life can certainly establish national character bulding based on the cultural creativity. Integrating cultural content in the products of creative industries is a breakthrough that will make the product unique and competitive as well as will preserve the noble values of the national culture.The method used in this activity is the dissemination of creative industries, local wisdom and product development withindigenous content. This activity also used simulation methods to give participants practical experience of  designing and manufacturing  creatively industrial products creative with content of local wisdom.After having held the dissemination of cultural creative industry development efforts based on local wisdom in South Pringsewu Sub District Pringsewu Regency, the understanding of the creative industries increased by 21.99%, the  understanding of local wisdom by 17.88% and the understanding of the development of products with the indigenous content by 44.14%. In addition all participants could also perform simulations corresponding stages of the process being simulated. Thus, this dissemination provides an enhance of the knowledge and skills of the trainee. In future, to further enhance the skills of the creative industries in designing products with local wisdom, the dissemination can be more focused on practices of  design and quality of the products.  Keywords : Culture, creative industries, local wisdom